Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelia TAHU pada UD. TAHU MURNI - Maria Magdalena Bate'e; Jenius Telaumbanua; Aferiaman Telaumbanua; Yuterlin Zalukhu (Visi Sosial Humaniora, 2025)
This research aims to determine the influence of product quality on tofu purchasing decisions at UD. Pure Tofu. The product quality in question includes several dimensions, namely durability, taste, cleanliness and packaging. Purchasing decisions are consumers' choices to buy products after considering various factors. The method used in this research is quantitative with a survey approach. The research sample consisted of 40 consumers who bought tofu at UD. Pure Tofu, which was selected using a purposive sampling technique. Data was collected through questionnaires and analyzed using simple linear regression. The research results show that product quality significantly influences the decision to purchase tofu at UD. Pure Tofu. Durability and taste variables have the strongest influence on purchasing decisions. Based on these results, it is recommended that UD. Tahu Murni focuses more on improving product quality, especially in the aspects of taste and durability, to increase customer satisfaction and encourage repeat purchases.